2003
DOI: 10.1519/1533-4287(2003)017<0167:pormih>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of 1 Repetition Maximum in High-School Power Lifters

Abstract: Eighteen elite male power lifters performed 1-repetition maximum (1RM) and submaximal strength tests (70, 80, and 90% 1RM) to develop prediction equations for the squat (SQ), bench press (BP), and deadlift (DL) exercises. For each equation, stepwise multiple-regression prediction procedure included the maximum number of repetitions (REPS) completed at a given %1RM weight (REPWT). For SQ and BP the 70% 1RM yielded the best 1RM prediction equations: (1RM SQ [kg]) = 159.9 + (0.103 x REPS x REPWT) + (-11.552 x REP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 7 publications
0
18
1
10
Order By: Relevance
“…Previous studies on the topic are equivocal, with some noting significant relationships of strength with FFM (26,27) and others finding a lack of relationship of structural dimension with strength (4,21). In this study, body composition did not seem to explain more than 55% of the variance in either 1RM or 28% in either work capacity.…”
Section: Discussioncontrasting
confidence: 77%
“…Previous studies on the topic are equivocal, with some noting significant relationships of strength with FFM (26,27) and others finding a lack of relationship of structural dimension with strength (4,21). In this study, body composition did not seem to explain more than 55% of the variance in either 1RM or 28% in either work capacity.…”
Section: Discussioncontrasting
confidence: 77%
“…Faigenbaum et al 52 evaluated the safety and efficacy of 1 repetition maximum (RM) testing in 96 children (6–12 years) and reported that healthy boys and girls can safely perform maximal effort strength tests on weight machines provided that appropriate testing procedures are followed. In other reports, children and adolescents safely performed 1 RM strength tests using free weights 36 37 53 54 55. These data suggest that children and adolescents can safely engage in this type of strength testing provided that appropriate loads are used, established guidelines are followed and qualified professionals are present.…”
Section: Incidence and Distribution Of Youth Resistance Training Injumentioning
confidence: 63%
“…5 Estimation of maximum squatting load (1RM) was used as an indication of muscle strength of lower limbs. 6 For the muscle power of lower limbs, vertical jumps (VJ), 7 condition with counter-movement and free movement of the arms, and Vertical Power Jump (VPJ), 7 condition with counter-movement and restriction of arm movement .The jump height was quantified by the Globus Systems ® (Globus Brasil, RJ, Brazil) with 0.001 s precision.…”
Section: Methodsmentioning
confidence: 99%